Duration of resuscitation efforts and long-term prognosis following in-hospital cardiac arrest (IHCA). (14th October 2021) - Yonis, H; Winkel, B; Andersen, M P; Wissenberg, M; Kober, L; Gislason, G; Larsen, J M; Folke, F; Pedersen, C T; Sogaard, P; Kragholm, K
Abstract: Background: The decision to terminate resuscitation efforts can be challenging. Notably, the association between duration of resuscitation and long-term survival and functional outcomes after in-hospital cardiac arrest (IHCA) is unknown. Purpose: To examine 30-day and 1-year survival stratified by duration of resuscitation efforts. Further, to report long term outcome (1-year survival) without anoxic brain damage or nursing home admission among 30-day IHCA survivors. Methods: We included all patients with IHCA from 13 Danish hospitals between January 1st, 2013 to December 31st, 2015. Patients were only included if there was clinical indication for a resuscitation attempt. Data on IHCA was obtained from the DANARREST database, which was linked to national registries to retrieve information on patient characteristics, survival, anoxic brain damage and nursing home admission. Patients were stratified into four groups (A-D) according to quartiles of duration of resuscitation efforts: Group A (<5 minutes), group B (5–11 minutes), group C (12–20 minutes) and group D (≥21 minutes). Using multivariable regression analysis, outcomes were standardized for patient age, sex, Charlson Comorbidity Index, witnessed arrest, monitored arrest, cardiopulmonary resuscitation (CPR) prior to arrival of the in-hospital cardiac arrest team and defibrillation. Results: The study population comprised of 1868 patients, median age was 74 (1st-3rd quartile [Q1-Q3] 65–81 years) and 65.0% were men. In total, 52.1% (n=973) of the patients achieved return of spontaneous circulation (ROSC). The overall median duration of resuscitation was 12 min (Q1-Q3 5–21 min). The standardized absolute chance of 30-day survival was 63.6% (95% CI 58.0%-69.0%) for group A, 34.0% (95% CI 29.7%-38.2%) for group B, 14.1% (95% CI 10.7%-17.5%) for group C and 9.0% (95% CI 6.8%-11.8%) for group D. Similarly, the chance of 1-year survival was highest for group A (51.5%; 95% CI 46.3%-56.7%) gradually decreasing to 7.0% (95% CI 4.5%-9.5%) in group D (Fig. 1). Among 30-day survivors of an IHCA, the standardized absolute chance of survival without anoxic brain damage or nursing home admission within one-year post-arrest was highest for patients resuscitated in group A (83.2%; 95% CI 78.4%-88.1%), decreasing to 72.3% (95% CI 64.5%-80.0%) in group B, 68.3% (95% CI 55.3%-81.2%) in group C and 71.1% (95% CI 54.2%-88.0%) in group D (Fig. 2). Conclusion: Short time to ROSC after in-hospital cardiac arrest is associated with better long-term prognosis. However, the majority of 30-day survivors are alive 1-year post-arrest without anoxic brain damage and without need for nursing home admission despite prolonged resuscitation. FUNDunding Acknowledgement: Type of funding sources: None.